ROTATION MATRIX-BASED ORIENTATION ESTIMATION USING INERTIAL MEASUREMENT UNIT - WINANDI (NIM : 13205150), HERRY
Development and the need for Unmanned Aerial Vehicle (UAV) in a few decades grew rapidly. Development in the field of communications, electronics, sensors, and computer technology supports the development of UAV significantly. The author choose orientation estimation system that can be implemented on the UAV as a topic because UAV’s business prospect as a military device or monitoring devices in general is considered to be very good. This final year project describes design and implementation of rotation matrix-based orientation estimation system using inertial measurement unit. Method used by the system is trying to represent the orientation of the aircraft with respect to the earth as a rotation. In general, the orientation estimation method is carried out through the rotation matrix calculation by using a gyroscope as the main source of information. Then the rotation matrix elements need to be renormalized through renormalization because there is numerical error exist in the elements created from the integration process. The final step is by doing drift correction using accelerometer signals and feedback controller. Drift correction at this final year project is only made for roll and pitch angle, while the yaw angle is not corrected because there is no additional reference component such as Global Positioning System (GPS) or magnetometer. This final year project also describes design of interface program by using Labview which can ease the system’s examination. The program receives data sent via serial communication with a microcontroller. The data is then used to represent the estimation of orientation through a cube that can rotate. The obtained-results show that the system meets the theorem and able to represent the orientation of the aircraft properly. This condition indicates a good prospect for the further development of orientation estimation system design.